ANALISIS BELANJA DAERAH KOTA BENGKULU TAHUN 2014-2017 (TINJAUAN EFISIENSI DAN EFEKTIVITAS) - Miftahul Hasanah; Merri Anitasari (Convergence: The Journal of Economic Development, 2019)
The purpose of this study was to determine the level of efficiency and effectiveness of regional government expenditure  in Bengkulu city. The analysis tools used to determine the implementation of regional government expenditure that is by using a descriptive elaboration which include; data reduction, data presentation, and  drawing conclusions/verification. Meanwhile,  to determine the level of effectiveness and efficiency of regional government expenditure, by using the ratio of the efficiency and effectiveness. The results of efficiency analysis of regional government expenditure showed that  the average of the calculation of the overall efficiency level formulation is 98%, this indicates that the level of efficiency is still low because the result is more than 80%. This suggests that local  government is  still wasteful  in using  the budget. The     results     of analysis     of the     effectiveness     of government spending  showed that the calculation of the effectiveness  of regional government expenditure  formulation of Bengkulu city in the period year of 2008 to 2017 fluctuate with the average  rate of effectiveness of 93%.  This  it  means that the level of effectiveness of regional government expenditure in the Bengkulu city is   already   effective,    this    is   indicated from the results of calculations which show figure more than 90%. Keywords: Efficiency and Effectiveness: Regional Finance, Regional Expenditure